Faktor Penentu Loyalitas Pelanggan PT Nabawi Mulia Pendekatan Kualitatif Dan Kuantitatif Menggunakan PLS SEM - Agus Djoko Sentosa; Dwi Sihono Raharjo; Rilla Sovitriana; Evi Nilawati; Nur Idaman (Universitas Persada Indonesia YAI, 2022)
Opportunities for the magnitude of consumer interest are utilized as optimally as possible by theorganizers of the umrah and hajj pilgrimage, taking into account the important factor is customerloyalty, customer loyalty is the driving force to go forward in supporting the development ofreligious tourism services. Customer loyalty, related to the perception of the perpetrators orconsumers, where the higher the services of the service institutions to the consumer, give a highvalue of behavior to recommend to others, in the form of written promotions, or through word ofmouth, called words to mouth. Many factors affect customer loyalty, including internal priceorganizers. Research on the factors that influence customer loyalty is approached by twocauldron methods and I use NVivo and PLS2. The main purpose of this study as a form ofservice in an effort to improve consumer service strategies at the Umrah and Hajj serviceinstitute, PT Nabawi Mulia.